COALITION EXISTENCE IN PRESIDENTIAL SYSTEM IN INDONESIA ACCORDING TO THE CONSTITUTION OF REPUBLIC OF INDONESIA 1945 - Beverly Evangelista (Fakultas Hukum Universitas Mataram, 2014)
Coalition Existence In Presidential System In Indonesia According To The Constitution Of Republic Of Indonesia 1945. The purposes of this research are to determine whether the coalition is conceptually consistent with presidential system according to the Constitution of Republic of Indonesia 1945, it influence to the governance and to the effectiveness check and balances mechanism in implementation of government activities in Indonesia. Researcher is using normative-method with statutory approach, conceptual approach and comparative approach. After compiling legal materials, researcher start perform the analysis of legal documents gradually, related to the issues. Analyses were performed with a consistent and systematic set of activities with a view to obtaining an answer to the existence of the coalition in the presidential system according to the Constitution of Republic of Indonesia 1945. The existence of the coalition in the presidential system in Indonesia is conceptually only intended on election system, not in governance system. In fact, coalition that built in the multi parry and presidential system as Indonesia is not appropriate and impact on governance leading to disharmony among coalition partners and ultimately affect the effectiveness of check and balances mechanism. Thus it can be concluded that, the practice of coalition in presidential system in Indonesia is contrary with the Constitution of Republic of Indonesia 1945. With regard to the impact, coalition in the presidential system is not appropriate. It will lead to disharmony relations among the coalition partners that affect the effectiveness of check and balances mechanism.Keywords : Coalition, Presidential, System